2003
DOI: 10.1101/gad.1110703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a DNA-binding site and transcriptional target for the EWS–WT1(+KTS) oncoprotein

Abstract: Desmoplastic small round cell tumor (DSRCT) is defined by a chimeric transcription factor, resulting from fusion of the N-terminal domain of the Ewing's sarcoma gene EWS to the three C-terminal zinc fingers of the Wilms' tumor suppressor WT1. Although DNA-binding sites have been defined for the uninterrupted WT1 zinc finger domains, the most prevalent isoforms of both WT1 and EWS-WT1 have an insertion of three amino acids [lysine, threonine, and serine (KTS)], which abrogates binding to known consensus sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…As for the downstream target of 17AA( þ )KTS( þ )WT1 isoform, we could not determine it. However, since this isoform has an insertion of three amino acids (lysine, threonine, and serine (KTS)), by which binding of 17AA( þ ) KTS( þ )WT1 isoform to a consensus sequence as that for 17AA( þ )KTS(À)WT1 isoform was abrogated, 17AA( þ )KTS( þ )WT1 isoform may transcriptionally regulate other gene(s) than one(s) regulated by 17AA( þ )KTS(À)WT1 isoforms (Reynolds et al, 2003). Comprehensive studies, including microarray analysis are being planned to identify the targets of 17AA( þ ) KTS( þ )WT1 isoform.…”
Section: Discussionmentioning
confidence: 99%
“…As for the downstream target of 17AA( þ )KTS( þ )WT1 isoform, we could not determine it. However, since this isoform has an insertion of three amino acids (lysine, threonine, and serine (KTS)), by which binding of 17AA( þ ) KTS( þ )WT1 isoform to a consensus sequence as that for 17AA( þ )KTS(À)WT1 isoform was abrogated, 17AA( þ )KTS( þ )WT1 isoform may transcriptionally regulate other gene(s) than one(s) regulated by 17AA( þ )KTS(À)WT1 isoforms (Reynolds et al, 2003). Comprehensive studies, including microarray analysis are being planned to identify the targets of 17AA( þ ) KTS( þ )WT1 isoform.…”
Section: Discussionmentioning
confidence: 99%
“…However, although a transcriptional role for a chimeric Ewing's Sarcoma gene (EWS)-WT1(+KTS) protein has been described (Reynolds et al 2003), no clear function has been attributed to the native WT1(+KTS) protein, in spite of the fact that proper +KTS/−KTS ratios are crucial in the development of several organs (Hammes et al 2001;Davies et al 2004;Wagner et al 2005). In this study, we have shown for the first time that WT1(+KTS) functions at the post-transcriptional level to regulate RNA expression and, specifically, that the +KTS protein can function in conjunction with a cis-acting CTE to promote translation of an unspliced RNA with a retained intron.…”
Section: Discussionmentioning
confidence: 99%
“…The most strongly upregulated gene was Lrrc15 [leucine rich repeat containing 15; also known as LRR-induced by ␤-amyloid (LIB)], which encodes a transmembrane protein of unknown function that localises to the leading edge of migrating cells (Reynolds et al, 2003;Satoh et al, 2002). It is interesting to note the upregulation of genes encoding ABL2, a tyrosine kinase implicated in cell motility (Woodring et al, 2003), ABI1 (ABLinteractor 1) and MAP4K4, a promigratory kinase (Collins et al, 2006).…”
Section: Induction Of Egfs In Taf4 Mutant Epidermismentioning
confidence: 99%